Answer:
multiply the left side of the constant vector by the inverse matrix
Explanation:
The matrix equation ...
AX = B
is solved by left-multiplying by the inverse of A:
A⁻¹AX = A⁻¹B
IX = A⁻¹B . . . . . the result of multiplying A⁻¹A is the identity matrix
X = A⁻¹B . . . . . B needs to be multiplied by the inverse matrix
![\left[\begin{array}{c}x&y\end{array}\right] = \left[\begin{array}{cc}-4&1\\3&2\end{array}\right]^(-1)\left[\begin{array}{c}9&7\end{array}\right]=(1)/(11)\left[\begin{array}{cc}-2&1\\3&4\end{array}\right]\left[\begin{array}{c}9&7\end{array}\right]=\left[\begin{array}{c}-1&5\end{array}\right]](https://img.qammunity.org/2020/formulas/mathematics/high-school/lwjwj2br8v572kk53hs18ko63dzy0kwe7r.png)